The French book trade in Enlightenment Europe. - Curran, Mark (Mark David) (French book trade in Englightenment Europe ;, 2018)
"This volume is a ground-breaking contribution to enlightenment studies and the international and cross-cultural history of print. The result of a five year research project, the volume traces the output and dissemination of books and how reading tastes changed in the years 1769-1794. Mapping the book trade of the Société Typographique de Neuchâtel (STN), a Swiss publisher-wholesaler which operated throughout Europe, the authors reconstruct the cosmopolitan elite culture of the later enlightenment, incorporating many engaging case studies. The STN's archives are uniquely rich in both detail and range, and while these archives have long attracted book historians (notably Robert Darnton, a leading scholar of the Enlightenment), existing work is fragmentary and limited in scope. By means of comparative study, the author considers the entire book market across Europe, making local, regional and chronological nuances, based on advanced taxonomies of subject content, author information, markers of illegality and much more. This volume is, in short, the most diverse and detailed study of the late 18th-century book trade yet, while offering fresh insights into the enlightenment."--